The boardwalk bookshop (Wheeler Publishing, Mira Books, Mira, 2022)
"When fate brings three strangers to a charming space for lease on the California coast, the Boardwalk Bookshop is born. Part bookstore, part gift shop, part bakery, it's a dream come true for Bree, Mikki and Ashley. But while their business is thriving, their personal lives are...not. Bree, wounded by brilliant but cold parents and her late husband's ultimate betrayal, has sworn to protect her heart at all costs. Even from Ashley's brother, a writer and adventurer who has inspired millions. He's the first man to see past Bree's barricades to her true self, which terrifies her. Mikki has this divorce thing all figured out--somehow, she's stayed friends with her ex and her in-laws...until a new man changes how everyone looks at her, and how she sees herself. Meanwhile, Ashley discovers that the love of her life never intends to marry. Can she live without being a wife if it means she can have everything else she's ever wanted? At sunset every Friday on the beach in front of the Boardwalk Bookshop, the three friends share a champagne toast. As their bond grows closer, they challenge one another to become the best versions of themselves in this heartachingly beautiful story of friendship, sisterhood and the transformative power of love"--

Buffalo Valley (Colecao Dakota, 4,, 2005)
Arriving in the small prairie town of Buffalo Valley in North Dakota to visit an old family friend while his reluctant fiancee makes up her mind, Vaughn Kyle encounters Carrie Hendrickson and soon everything he once thought he wanted is called into question.

Paranoia (St. Martin's Press, 2004)
Trapped in a job he hates, Adam Cassidy, a young employee at a high-tech corporation, is caught attempting to manipulate the system and is offered a choice--prison, or spying at the headquarters of their competitor, Trion Systems.

Out of nowhere (Hachette Audio, Grand Central, Grand Central Large Print, 2023)
Brought together by a mass shooting at a Texas county fair, children's book author and single mother Elle Portman and high-rolling corporate consultant Calder Hudson, both fueled by revenge, search for a killer while wondering if the attraction growing between them is too painful and complicated to sustain.

Saturday night at the Lakeside Supper club: a novel (Pamela Dorman Books/Viking, 2023)
"This novel is the story of Mariel and Ned, a couple from two very different restaurant families in rustic Minnesota, and the legacy of love and tragedy, of hardship and hope, that unites and divides them"--

The vineyard at painted moon (HQN, 2021)
Devastated by a divorce that she admits was inevitable, MacKenzie finds her attempts to move away from the only family and source of employment she has ever known complicated by an unplanned pregnancy.

My not so perfect life: a novel (Thorndike Press large print basic, ,, 2017)
"When Katie Brenner is fired from her dream job in advertising in London, she's desperate to get away from her mad boss Demeter, and her crush, Alex, who she thought shared her feelings of adoration but didn't. Seeking refuge, she goes home to her father's farm in Somerset to help make her stepmother's dream of turning their land into a camping retreat come true. Applying her savvy marketing smarts, Katie masterminds a glamorous upscale resort. But when Demeter shows up unannounced, with Alex not far behind, Katie is forced to rethink her revenge fantasies and her assumptions about family, love, and office politics and realize how much she may have misjudged everyone--and everything--around her"--

Vanished (Series Nick Heller, 1,, 2009)
After an assault leaves his estranged brother nowhere to be found and his sister-in-law in a coma, security investigator and ex-intelligence agent Nick Heller is forced to contend with one of the most powerful and secretive corporations in the world.

Poison: a novel (Atria Books, 2018)
After the owner of a successful family business is murdered, attorney Dismas Hardy, who doubts the guilt of the chief suspect, navigates the dangerous secrets and gold-digger agendas to identify the killer.

I still dream about you: a novel (Random House Large Print, Random House, 2010)
Real estate agent Maggie Fortenberry works at Red Mountain Reality, that has been going downhill since the death of its founder, comes up with a plan to save the business. The rival of their company Babs is unscrupulous real estate agent who hates Maggie and is determined to put her out of business.

Fulfillment (Severn House, 2018)
Diandra Casey and Gregory York are childhood rivals and longtime adversaries, both vying for the same powerful position at one of the country's most elite department stores.

The Devine Doughnut Shop (Montlake, 2023)
When a smooth-talking developer wants to buy their Devine Doughnut Shop, Grace, Sarah, and Macy find their beloved heritage up for grabs and their future up in the air until a little determination, a sprinkle of sass, and the promise of romance are added into the mix.

Kingdom come (Warner Books, 2006)
Having made his construction company into a multi-billion dollar corporation, James King reveals a massive public offering that would render him CEO for life, prompting his second-in-command's wife to plot his murder.

Come sundown (Thorndike Press large print basic, ,, 2017)
"A novel of suspense, family ties, and twisted passions from the #1 New York Times bestselling author of The Obsession... The Bodine ranch and resort in western Montana is a family business, an idyllic spot for vacationers. A little over thirty thousand acres and home to four generations, it's kept running by Bodine Longbow with the help of a large staff, including new hire Callen Skinner. There was another member of the family once: Bodine's aunt, Alice, who ran off before Bodine was born. She never returned, and the Longbows don't talk about her much. The younger ones, who never met her, quietly presume she's dead. But she isn't. She is not far away, part of a new family, one she never chose--and her mind has been shattered... When a bartender leaves the resort late one night, and Bo and Cal discover her battered body in the snow, it's the first sign that danger lurks in the mountains that surround them. The police suspect Cal, but Bo finds herself trusting him--and turning to him as another woman is murdered and the Longbows are stunned by Alice's sudden reappearance. The twisted story she has to tell about the past--and the threat that follows in her wake--will test the bonds of this strong family, and thrust Bodine into a darkness she could never have imagined"--

Marrying the ketchups: a novel (Alfred A. Knopf, 2022)
"An irresistible comedy of manners about three generations of a Chicago restaurant family and the private jokes, ancient grudges, broken hearts, and deep, abiding love that feeds them all"--

Simply vanished (Sugarcreek Amish mysteries, 8,, 2015)
As Cheryl Cooper's birthday approaches, she believes her new life in Sugarcreek, Ohio, is the best gift she's ever received. She loves running the Swiss Miss gift shop and even though there have been a few bumps along the way, she feels content. But an unexpected discovery in an abandoned laundry chute raises disturbing questions that could point to a woman who disappeared decades ago. Could she have been murdered? Is there a connection between her and the building that houses the beloved shop? As Cheryl begins a search for answers, her parents and brother come to town for a visit. Family tensions and disturbing clues from the past mix together to send her down a path that will challenge her personal relationships and finally solve an old mystery.

Tomorrow, and tomorrow, and tomorrow: a novel (Alfred A. Knopf, 2023)
"A modern love story about two childhood friends, Sam, raised by an actress mother in LA's Koreatown, and Sadie, from the wealthy Jewish enclave of Beverly Hills, who reunite as adults to create video games, finding an intimacy in digital worlds that eludes them in their real lives, from the New York Times best-selling author of The Storied Life of A.J. Fikry"-- On a bitter-cold day, in the December of his junior year at Harvard, Sam Masur exits a subway car and sees, amid the hordes of people waiting on the platform, Sadie Green. He calls her name. For a moment, she pretends she hasn't heard him, but then, she turns, and a game begins: a legendary collaboration that will launch them to stardom. These friends, intimates since childhood, borrow money, beg favors, and, before even graduating college, they have created their first blockbuster, Ichigo. Overnight, the world is theirs. Not even twenty-five years old, Sam and Sadie are brilliant, successful, and rich, but these qualities won't protect them from their own creative ambitions or the betrayals of their hearts. Spanning thirty years, from Cambridge, Massachusetts, to Venice Beach, California, and lands in between and far beyond, Gabrielle Zevin's Tomorrow, and Tomorrow, and Tomorrow is a dazzling and intricately imagined novel that examines the multifarious nature of identity, disability, failure, the redemptive possibilities in play, and above all, our need to connect: to be loved and to love. Yes, it is a love story, but it is not one you have read before.
Sick kids , Influences , Unfair games , Both sides , Pivots , Marriages , The NPC , Our infinite days , Pioneers , Freights and grooves.

Whirlwind (Champions, 01,, 2020)
"At the Alamo Canyon Ranch, set amid the desert foothills of Southern Arizona, the Champion women carry on the family legacy of breeding bucking bulls for the rodeo. In a world where bloodline is everything, love is the only risk worth taking ... Everyone's talking about Whirlwind at this year's Professional Bull Rider's Competition. But the promising young bull is the last thing on Shane Tully's mind once he lays eyes on the lady responsible for bringing Whirlwind to the arena. Beautiful, smart, and sexy as hell, Lexie Champion has this rodeo man hungry for more than the thrill of his next competition. But the daughter of bull rancher Bert Champion wants nothing to do with a daredevil, despite the powerful attraction between them ... After losing her beloved brother to a bull riding accident, Lexie is no stranger to the dangers of rodeo life. Which is why resisting Shane's rugged allure should have been easy. But nothing is simple about her reaction to the handsome cowboy, from their first kiss, to the terrifying moment Lexie watches Shane go down in the ring. Faced with a devastating decision, will Lexie make the ultimate sacrifice for the sake of love?"--

Daddy's gone a hunting (Thorndike Press large print basic, ,, 2013)
When her sister is wrongly implicated in an explosion that has destroyed her family's priceless antiques business and killed an employee, Hannah struggles to find clues in the ashes and discovers a life-threatening secret from the past.

Impostor syndrome: a novel (Custom House, 2021)
"In 2006 Julia Lerner is living in Moscow, a recent university graduate in computer science, when she's recruited by Russia's largest intelligence agency. By 2018 she's in Silicon Valley as COO of Tangerine, one of America's most famous technology companies. In between her executive management (make offers to promising startups, crush them and copy their features if they refuse); self promotion (check out her latest op-ed in the WSJ, on Work/Life Balance 2.0); and work in gender equality (transfer the most annoying females from her team), she funnels intelligence back to the motherland. But now Russia's asking for more, and Julia's getting nervous. Alice Lu is a first generation Chinese American whose parents are delighted she's working at Tangerine (such a successful company!). Too bad she's slogging away in the lower echelons, recently dumped, and now sharing her expensive two-bedroom apartment with her cousin Cheri, a perennial "founder's girlfriend". One afternoon, while performing a server check, Alice discovers some unusual activity, and now she's burdened with two powerful but distressing suspicions: Tangerine's privacy settings aren't as rigorous as the company claims they are, and the person abusing this loophole might be Julia Lerner herself. The closer Alice gets to Julia, the more Julia questions her own loyalties. Russia may have placed her in the Valley, but she's the one who built her career; isn't she entitled to protect the lifestyle she's earned? Part page-turning cat-and-mouse chase, part sharp and hilarious satire, Impostor Syndrome is a shrewdly-observed examination of women in tech, Silicon Valley hubris, and the rarely fulfilled but ever-attractive promise of the American Dream."--Publisher.